The Peripheral Sympathetic Neuron is Intact in Alzheimer's Disease and Behavioral Variant of Frontotemporal Dementia. (June 2015) - Struhal, Walter; Javor, Andrija; Benesch, Thomas; Vosko, Milan R.; Ransmayr, Gerhard
Introduction: The study was undertaken to evaluate the postganglionic sympathetic sudomotor function employing the quantitative sudomotor axon reflex test (QSART) in tauopathies Alzheimer's disease (AD) and behavioral variant of frontotemporal dementia (bvFTD). Methods: Patients were recruited in a prospective pilot study. A structured history was taken and QSART was recorded. Results: In all, 15 patients with AD (7 female) and 14 patients with bvFTD (9 female) were included. Mean age (±standard deviation) of patients with AD and bvFTD was 74 ± 9 and 71 ± 10 years, respectively. Severe sudomotor dysfunction (Composite Autonomic Severity sudomotor score 3) was present in 3 (20%) patients with AD and 0 (0%) patients with bvFTD ( P = .037). The upper extremity was only involved in 1 patient with AD and 1 patient with bvFTD. Sweat results of the 4 recording sites did not differ between both groups. Patients' history correlated with severe autonomic symptoms as assessed with QSART. Conclusion: Postganglionic sudomotor involvement in AD and bvFTD is most likely not part of the disease.